Cedera Saraf Setelah Anestesi Neuraksial Nerves Injury Post Neuroaxial Anesthesia - Doso Sutiyono (Jurnal Komplikasi Anestesi, 2014)
Neural injury post neuroaxial anesthesia procedure is a rare complication but feared by many anesthesiologists. Neural injury incidence range is 0,03 to 0,1% among all neruaxial block patients. Neural injury is happened due to infection, needle-trauma to vertebrae or vertebral neural cord directly, medulla spinalis ischaemia or neurotoxicity. Most causes of neural injury are hematoma and infection. Whenever suspect a neural injury, rapid diagnosis and treatment are needed. MRI and CT-scan examination are the best of choice in imaging neural injury. Mild symptoms without objective neural deficit, mostly showed good prognosis and whenever they are deteriorate, a neurologic consultation must be done. Lesion with moderate or severe deficit neulogic is an indication for advanced neurologic consultation, neurophysiologic examination (neural conduction study and electromyography) or MRI/CT Scan examination. A complete or progressive neural deficit needs to be evaluated by a neurologist or neurosurgeon. Neural injury with mild symptoms can be treated with steroid, NSAID, neurotropic vitamins, and physiotherapy. Neural trauma due to compression, needs to be decompressed. Recovery process has a direct relationship with the early decompression treatment.